Lack of phosphomannomutase 2 affects Xenopus laevis morphogenesis and the non-canonical Wnt5a/Ror2 signalling - Himmelreich, Nastassja; Kaufmann, Lilian; Steinbeisser, Herbert; Körner, Christian; Thiel, Christian (Journal of inherited metabolic disease, 2015)
Reduced phosphomannomutase 2 activity in man leads to hypoglycosylation of glycoconjugates causing PMM2-CDG, the most common type of congenital disorders of glycosylation. Here we show that an antisense morpholino-mediated knockdown of the Xenopus laevis phosphomannomutase 2 gene provoked a general underglycosylation in frog embryos, which led to an altered phenotype and reduced glycosylation of Wnt5a as member of the non-canonical Wnt signalling. Loss of function experiments in hemi-sectioned embryos proved that due to the phosphomannomutase 2 knockdown expression of the Wnt5a/Ror2 target gene paraxial protocadherin was significantly decreased. Regarding the expression of paraxial protocadherin, a gain of function could only be achieved by injections of wnt5a and ror2 in dorsal neighbouring blastomeres, while a parallel injection of phosphomannomutase 2 morpholino led to a significant reduced level of expression. Our data show for the first time that a knockdown of phosphomannomutase 2 influences in vivo the non-canonical Wnt signalling during early embryogenesis.